PENGARUH PEMANFAATAN MEDIA BAHAN ALAM TERHADAP KEMAMPUAN GERAKAN MANIPULATIF ANAK USIA 4-5 TAHUN DI PAUD SPNF SKB PALEMBANG - Mahera, Nadia; Suningsih, Taruni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Manipulative movement is an important aspect in children's motor development, because it plays a role in shaping children's abilities in cutting, stringing, grasping, and forming various objects. This study aims to determine the effect of activities utilizing natural materials on manipulative movement abilities in children aged 4-5 years at PAUD SPNF SKB Palembang. The research method used in this study is quantitative using an experimental type and one-shot case study design. Data collection techniques in this study were carried out through observation using a checklist and documentation. The instrument used contains indicators of children's manipulative movement abilities that cover four aspects, namely cutting, stringing, grasping, and forming, and has been declared valid and reliable. The sample used was 15 children aged 4-5 years, the sampling technique used a total sampling technique. The results of data analysis in the normality test that has been carried out show a posttest significance value of 0.162 which is greater than 0.05 (sig. > 0.05) so it can be concluded that the data is normally distributed. Furthermore, in the t-test, the calculated t value was 5.371 and the t-table result was 1.761. Based on the calculation, it can be concluded that the calculated t > t table (5.371 > 1.765) so that Ho is rejected and Ha is accepted. This shows that there is an influence of the activity of utilizing natural material media on manipulative movements in children aged 4-5 years in PAUD SPNF SKB, which has been empirically proven and can be used as a stimulation for the development of children's manipulative movement abilities.